Growing Strategic Alliance between India and USA: Implications on Pakistan - Kabeer Khan, Muhammad; Rafeeq, Rifat; Imran Ashraf, Muhammad (Annals of Human and Social Sciences, 2022)
This research aims at critically analyzing the growing Indo-US strategic allaince and consequences for Pakistan. This study explores background factors of today’s Indo-US strategic alliance that by the time when United States emerged as a sole super power of the world, how New Delhi rearranged her diplomatic policies regarding foreign relationship and so on shifted her policy of non-alignment into the start of new era of strategic development with USA and other concerning states. USA also welcomed India whole heartedly as USA got a firm stage to drive the policies of South Asia in the form of India as strongest partner of 21st century. This qualitative study is based on content analysis of relevant documents, speeches and government reports. Further, through detailed content analysis this study finds out that to keep check on economic development of China and strong alliance of China with Pakistan, India proves as a major check base for USA due to growing strategic alliance. As fruitful results, India is on the way of strong armament by the assistance of USA and consequently Pakistan is facing negative implications in this regard. The study proposes a way forward for Pakistan to deal with this challenge by adopting a pragmatic foreign policy approach.